Showing Our Colors : Afro-German Women Speak Out - Schultz, Dagmar; Oguntoye, Katharina; Ayim, May, 1960-1996 (Book collections on Project MUSE., 1992)
Precolonial images of Africa, colonialism, and fascism -- The Germans in the Colonies -- African and Afro-German women in the Weimar Republic and under National Socialism -- Our father was Cameroonian, our mother, East Prussian, we are mulattoes / Doris Reiprich and Erika Ngambi Ul Kuo -- An "occupation baby" in postwar Germany / Helga Emde -- "Aren't you glad you can stay here?" / Astrid Berger -- "Mirror the invisible, play the forgotten" / Miriam Goldschmidt -- Three Afro-German women in conversation with Dagmar Schultz / Laura Baum, Katharina Oguntoye, May Optiz[sic] -- "What makes me so different in the eyes of others?" / Ellen Wiedenroth -- Old Europe meets up with itself in a different place / Corinna N. -- "All of a sudden, I knew what I wanted" / Angelika Eisenbrandt -- "I do the same things that others do" / Julia Berger -- Mother: Afro-German, Father: Ghanaian / Abena Adomako -- The break / May Optiz[sic] -- What I've always wanted to tell you / Katharina Oguntoye -- "I never wanted to write, I just couldn't help myself" / Raya Lubinetzki